Detection of chronic wasting disease prions in soil at an illegal white-tailed deer carcass disposal site - Madeline K. Grunklee; Stuart S. Lichtenberg; Nicole A. Lurndahl; Marc D. Schwabenlander; Diana L. Karwan; E. Anu Li; Jason C. Bartz; Qi Yuan; Peter A. Larsen; Tiffany M. Wolf (Prion)
Chronic wasting disease (CWD) is a contagious prion disorder affecting cervids such as deer, elk, caribou, and moose, causing progressive and severe neurological degeneration followed by eventual death. As CWD prions (PrPSc) accumulate in the body, they are shed through excreta and secreta, as well as through decomposing carcasses. Prions can persist in the environment for years, posing significant concerns for ongoing transmission to susceptible cervids and pose an unknown risk to sympatric species. We used a validated protocol for real-time quaking-induced conversion (RT-QuIC) in vitro prion amplification assay to detect prions in soil collected within and around an illegal white-tailed deer (Odocoileus virginianus, WTD) carcass disposal site and associated captive WTD farm in Beltrami County, Minnesota. We detected PrPSc in 26 of 201 soil samples across 15 locations within the illegal disposal site and one on the farm that housed the cervids. Importantly, a subset of RT-QuIC positive soil samples was collected from soils where carcasses were recovered, providing direct evidence that environmental contamination resulted from this illegal activity. These findings reveal that improper cervid carcass disposal practices may have important implications for ongoing CWD transmission through the environment.